Estudo sísmico no açude Tucunduba, Senador Sá, CE - França, George Sand Leão Araújo de (1999)
The Tucunduba Dam, is west of Fortaleza, Ceará State. The seismic monitoring of the area, with an analogical station and seven digital stations, had beginning on June 11, 1997. The digital stations, operated from June to November 1997. The data collected in the period of digital monitoring was analyzed for determination of hypocenters, focal mechanisms, and shear-wave anisotropy analysis. For determination of hypocenters, it was possible to find an active zone of nearly 1 km in length, with depth between 4.5 and 5.2 km. A 60AZ/88SE fault plane was determined using the least-squares method and hypocenters of a selected set of 16 earthquakes recorded. Focal mechanisms were determined, in the composite fault plane solution, a strike-slip fault, trending nearly E-W, was found. Single fault plane solutions were obteined to some earthquakes presented mean values of 65 (azimuth), and 80 (dip). Shear-wave anisotropy was found in the data. Polarization directions and travel time delays, between S spliting waves, were determined. It was not possible to obtain any conclusion on the cause of the observed anisotropy. It is not clear if there is correlation between seismicity and mapped faults in the area, although the directions obtained starting from the hipocentros and focal mechanism are they are consistent with directions, observed in the area, photo, topographic and fractures directions observed in the area